Teachers' Mindset on Gender Responsive Pedagogy (GRP) in Mathematics Classroom - Adhikari, Hom Kumari (Curriculum Development Journal, 2021)
The purpose of this study was to analyze mathematics teachers' mindset regarding GRP practices in their classroom set up and classroom activity at secondary school level. The respondents were 120 mathematics teachers (106 male, 14 female), who were teaching mathematics at grade IX and X and were selected randomly. The participants were from three districts: Kathmandu, Sindhuli, and Chitwan of Province Three of Nepal. Cross-sectional Survey design was employed for this study. Self- developed questionnaire was considered as the data collection tool. The collected data were analyzed using descriptive statistics (Mean and Standard Deviation) and inferential statistics (One Sample t-test). The result of the study indicated that secondary level mathematics teachers are practicing GRP on classroom set up and classroom activity. However, they did not give more time and effort for girls for learning mathematics and low practice of group work for cooperative learning, which is important for reducing gender bias and empower girls in learning mathematics. The Government of Nepal should provide teachers GRP awareness training about how to practice GRP in classroom through policy and changing concept in school curriculum and promote positive mindset towards GRP practice.